Mosque Community: Economic Empowerment and Legal Counseling (Strengthening the â€œThoriqul Hudaâ€ Mosque Congregation in Dorokenong Hamlet, Tulung Village, Sampung District, Ponorogo Regency) - Anwar Mujahidin; Kelik Wardiono; Erwin Yudi Prahara; Arief Budiono; Dewi Iriani (Masyarakat Berdaya dan Inovasi, 2021)
The mosque is not only a place for congregation to pray five times a day. Mosques have social, educational and even economic functions. LP3M IAIN Ponorogo has developed mosque posdaya with the aim of empowering the community on the basis of a mosque. The principle of empowerment used is emancipatory, which is to organize the community by placing the community as the subject (subject) with the empowerment paradigm that rests on the community (community based development). The program called the mosque's Posdaya is centered at the Thoriqul Huda mosque, Dorokenong Hamlet, Tulung Village, Sampung Ponorogo District. The revitalization of the function of the Thoriqul Huda mosque is carried out by empowering the economy of congregations who are economically disadvantaged or called pre-prosperous communities. Economic empowerment activities are manifested through entrepreneurship training activities for plastic bag making and marketing. The activity is aimed at providing life skills for preprosperous families of mosque congregations. In the next stage, improving the life skills of congregations from underprivileged families must be supported by capital and network access. Mosques develop amil zakat institutions and mosque cooperatives by strengthening mosque religious management.